(untitled) (Bangladesh Journal of Medical Biochemistry, 2018)
Diabetic patients frequently develop a constellation of electrolyte disorders. These derangement results from insulin deficiency, hyperglycemia and hyperketonemia. Hyperglycemia sets the internal environment for osmotic diuresis while causing a dilutional effect on electrolyte concentrations.The osmotic effect of glucose results in decreased circulating blood volume and fluid shift from the intracellular spaces causing cellular dehydration. These disturbances are particularly common in decompensated diabetes, especially in the context of diabetic ketoacidosis or non ketotic hyperglycemic hyperosmolar syndrome.These patients are markedly sodium, magnesium and phosphate depleted. Diabetes mellitus is linked to both hypo and hyperkalemia and also hypo and hypercalcemia reflecting coexistence of hyperglycemia related mechanisms, which tend to change serum potassium and calcium to opposite directions. This article provides an overview of the electrolyte disturbances occurring in Diabetes and mechanisms underlying those disturbances. Bangladesh J Med Biochem 2017; 10(1): 27-35